To Dwell and To Reinhabit: Kiana Davenports’s House of Many Gods as Bioregional Literature - Kristiawan Indriyanto (Faculty of Social and Political Sciences University of Bangka Belitung, 2018)
Environmental degradation has become a pivotal issue in Hawaiâi nowadays. The policies of United Statesâgovernment and military has shaped the Hawaiâian ecology. Through the process of ecological imperialism,started from the beginning of American colonialism, both the Hawaiâianâs landscape and their connection withthe environment is disrupted. Modern Hawaiâian ecology nowadays is a postcolonial ecology, which was, andstill is molded by the American imperial power. As a product of colonialism, Hawaiâiansâ have becomealienated with their ancestral traditions, especially regarding interrelation between human and non-human.Taking cues from Lawrence Buellâs assertion that environmental crisis is a crisis of the imagination, modernHawaiâian literature tries to reorient humanânon human relationship from indigenous Hawaiâianepistemology. As seen in Kiana Davenportâs the House of Many Gods, traditional Hawaiâian perspective isreimagined to reterritorialize Hawaiâians in their previous environmental outlook, before the arrival of theAmericans. This study argues that by several bioregional concepts such as dwelling, and reinhabit, KianaDavenportâs the House of Many Gods can be stated as a bioregional literature.